Prevention of bacterial colonization of intravenous catheters by antiseptic impregnation of polyurethane polymers - Bach, Alfons; Böhrer, Hubert; Motsch, Johann; Martin, Eike; Geiss, Heinrich K.; Sonntag, Hans-Günther (The journal of antimicrobial chemotherapy, 1994)
The use of intravascular catheters is associated with infectious complications. Using plastic materials with antibacterial activity may reduce catheter-related bacterial colonization. A novel intravascular catheter impregnated with the antiseptics silversulphadiazine and chlorhexidine was tested in an in-vivo model using implantation of catheters into the internal jugular veins of rats. The rate and magnitude of bacterial colonization in groups with implantation of silver-sulphadiazine and chlorhexidine bonded (SSC) and control (C) catheters were assessed 3 and 7 days after intravenous implantation, and local challenge at the exit site by 107 cfu Staphylococcus epidermidis ATCC 35984. Significant reductions in the culture positivity of catheters were observed in the test compared with control groups. After 3 and 7 days, the magnitude of bacterial colonization of implanted catheter segments was significantly lower compared with control catheters (P < 0·01). These findings indicate that antiseptic-bonded catheters substantially reduce the incidence and magnitude of catheter-related bacterial colonization, and may subsequently reduce catheter-related infection.